The overview of green building sector in Slovakia - Golej, Julius; Adamuscin, Andrej (EAI Endorsed Transactions on Energy Web, 2019)
Green buildings have become a global trend in recent years, reflecting a social order for sustainable development from the sides of all stakeholders. This is confirmed by the fact that the global construction of green buildings comprises for almost a quarter of the total production of all buildings. Buildings generally represent a huge sector of energy consumers, so it is now necessary to reduce this consumption through smart design solutions and an appropriate building management system that will ensure efforts to achieve sustainable and smart urban requirements for the use of intelligent technologies. Regarding to the development of green buildings, Slovakia belongs to developing countries. The term "green building" is slowly becoming familiar in Slovakia, although it should be noted that the green building certification systems are only at the beginning. Also, the legislative and other financial support instruments for green buildings in Slovakia are under the phase of consideration and do not exist in practice. In the following paper, the authors explore green building sector in Slovakia. They present their development and overview, rating systems and analyses the most important investors and key local companies related to green buildings in Slovakia.
Keywords: green building; Slovakia; rating systems; LEED; BREEAM